Perlindungan Hukum Terhadap Barang atau Merek KW Di Indonesia - Luthfi Al Qarani Muhammad Taufik; Marni Emmy Mustafa; Farhana Farhana (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The period of global trade, in accordance with Indonesia's ratification of international accords. As the role of the brand becomes increasingly significant, particularly in ensuring healthy business rivalry, adequate brand regulation is required to deliver community services. Trademark is a subset of Intellectual Property Rights, in which the brand provides a specific amount of value to the circulation of goods. In tandem with a rise in market demand, the development of the circulation of items with in-demand brands will increase, as will the requirements and lifestyles of the community. Frequently, business actors infringe the mark in order to meet the price and quality requirements of the community with counterfeit or KW goods. So that the establishment of unhealthy companies conducted by unlicensed business actors of counterfeit goods. The existence of infractions in the society necessitates legal protection for brand owners. The author employs a qualitative research approach and normative research in this study. Legal protection against counterfeit goods or KW and consumer protection has been regulated in Indonesian laws and regulations, according to the study's findings.